MATERI PELAJARAN PERSPEKTIF HADITS - Maslani Maslani; Ratu Suntiah (Jurnal Perspektif, 2019)
The purpose of writing this article to reveal what urgent material to be conveyed in Islamic education. Hadith as a guideline of Muslims has a very important role in guiding the subject matter that must be delivered in learning. The analytical method used is based on the qualitative model by using causal analysis approach. Based on the results of research can be seen that the subject matter in Islamic educational institutions still cross opinion. To be able to know the material that needs to be submitted in the educational process, it is necessary to trace the subject matter perspective al-Hadits.